Linking empowering leader to creativity: the moderating role of psychological (felt) empowerment - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
One of the challanges of today's organizations is creating a corporate culture which promotes employee creativity and innovation. For creativity to occur in organizations, leaders have considerable influence over the context within which creativity can ocur. Synthesizing theories of leadership, creativity, and psychological (felt) empowerment, this empirical paper investigates (a) whether an empowering leader can encourage creativity; and (b) whether subordinates' psychological (felt) empowerment will moderate the ralationship between empowering leadership and creativity. Survey data were collected from 218 employees in technology and service sector and the obtained data from the questionnaires were analyzed through the SPSS 16.0. Analyses results revealed that empowering leadership positively affected employee creativity. In addition, employees' felt empowerment moderated this link. Leaders' empowering behaviors have a stronger impact on perceived creativity when employees feel empowered than when such psychological state of mind is low. Theoretical and cultural implications of the findings were also discussed.
Keywords: Empowering leadership; employee creativity; psychological (felt) empowerment; WORK-ENVIRONMENT; TRANSFORMATIONAL LEADERSHIP; EMPLOYEE CREATIVITY; MANAGEMENT TEAMS; MODEL; PERFORMANCE; BEHAVIORS; INNOVATION; SATISFACTION; VALIDATION